REQUIREMENTS FOR THE SPORT OF FOOTBALL AND METHODS OF ORGANIZING AND HOLDING FUDBOL COMPETITIONS - Mamayusupov Otabek (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article analyzes the requirements for football sports and the methodology for organizing and conducting fudbol competitions